PREVALENCE AND RISK FACTORS ASSOCIATED WITH WHEEZING IN YOUNG CHILDREN LESS THAN 5 YEARS OF AGE: A RETROSPECTIVE STUDY. - Varshini Chandrasekhar; Ashika Banu; Shami Kumar; Mohammed Syed (Student's Journal of Health Research, 2023)
Objective: To identify risk factors that may contribute to recurrent wheezing in infants under the age of five. Material and Method:  In the Outpatient Department of Saveetha Medical College and Hospital, Chennai, a cross-sectional investigation was conducted on children younger than 5 years old. The study group consisted of fifty infants with symptoms and signs of recurrent wheezing. All of the parents filled out the questionnaires provided. To comprehend the characteristics of the study groups, a statistical analysis of descriptive data was conducted. The risk factors were analyzed using bivariate and multivariate statistical analyses that included all significant predictors with a p<0.05 level of statistical significance. Results: Upper respiratory tract infection [odds ratio (OR) 7.273; 95% confidence interval (CI) 2.277-23.232], lower respiratory tract infection [OR 5.332; 95% CI 2.326-12.225], passive smoking [OR 2.368; 95% CI 1.094-5.129], and daycare centre attendance [OR 2.590; 95% CI 1.168-5.745] were risk factors for recurrent wheezing, as determined by bivariate analysis. Lower respiratory tract infection [adjusted odds ratios (aOR) 0.241; 95% confidence interval (CI) 0.088-0.659] was the most relevant risk factor for recurrent wheezing, according to multivariate logistic regression analysis. Conclusion: Lower respiratory tract infection, upper respiratory tract infection, and passive smoking were identified as risk factors for recurrent wheezing in children under the age of five, with lower respiratory tract infection being the most significant risk factor. Targeted surveillance of these risk factors ought to reduce the frequency of recurrent breathlessness. This is particularly essential for patients at high risk, such as asthma patients.